2009
DOI: 10.1007/s00268-009-9938-0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Knowledge, Attitudes, Behavior, and Associated Factors Among Chinese Male Surgeons

Abstract: Background The purpose of this study was to understand and assess the smoking knowledge, attitudes, behavior, and associated factors among Chinese male surgeons. Methods A total of 823 Chinese male surgeons from six cities in China participated in a survey of smoking knowledge, attitudes, and behaviors in 2004. This study presents descriptive statistics and logistic regression analyses of factors associated with the respondents' smoking behavior and smoking cessation activity. Results The current smoking preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…[15] These results were better than that study by Yao et al .,[16] which found that only 25% of the respondents always asked patients about their smoking status whereas only 27.2% advised smokers to quit smoking. [16] But worse than other study conducted by McIlvain et al .,[14] in University of Nebraska; concerning physician attitudes and the use of office-based activities for tobacco control, found that the five skills most often used were recommending pharmaceutical aids (96%), giving advice to quit (93%), discussing barriers to and/or resources for smoking cessation (74%), informal contracting for specific behavior change (53%), and scheduling follow-up (43%). However, according to the US Public Health Service clinical practice guideline of using the 5 As, “all patients need to be at least asked about their smoking status and advised to quit”.…”
Section: Discussionmentioning
confidence: 83%
“…[15] These results were better than that study by Yao et al .,[16] which found that only 25% of the respondents always asked patients about their smoking status whereas only 27.2% advised smokers to quit smoking. [16] But worse than other study conducted by McIlvain et al .,[14] in University of Nebraska; concerning physician attitudes and the use of office-based activities for tobacco control, found that the five skills most often used were recommending pharmaceutical aids (96%), giving advice to quit (93%), discussing barriers to and/or resources for smoking cessation (74%), informal contracting for specific behavior change (53%), and scheduling follow-up (43%). However, according to the US Public Health Service clinical practice guideline of using the 5 As, “all patients need to be at least asked about their smoking status and advised to quit”.…”
Section: Discussionmentioning
confidence: 83%
“…Men comprised ≥50% of the sample in most of the studies. Three studies focused only on male physicians 18 35 36…”
Section: Resultsmentioning
confidence: 99%
“…For example, the lowest rate (14%) reported by Zhang et al 33 had a sample size of 141, while Ye et al 13 reported the highest smoking rate (64%) in their study with 503 subjects. Similarly, Yao et al 18 only studied male physicians. Overall, the prevalence of current smoking among Chinese physicians is high, especially among male physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest a lower awareness of tobacco control measures, generally, given that a recent study from Beijing [23] reported low levels of knowledge among doctors regarding the effects of smoking on Tuberculosis (TB), while many did not view smoking cessation as an integral part of TB treatment for their patients. Similarly, smoking among Chinese doctors is not necessarily a secretive behaviour, with one study reporting that almost 90% of health care providers who smoked did so in the wards, [13] while another study reported that 43% of Chinese surgeons had smoked in front of their patients [14]. …”
Section: Discussionmentioning
confidence: 99%